PENGARUH TINGKAT KEPADATAN PENGUNJUNG TERHADAP PEDAGANG KAKI LIMA ALUN-ALUN KOTA PROBOLINGGO - Andhi Nur Rahmadi; Irma Nur Cahya Setyowati; M. Rizky Hidayatullah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
From this research activity aims to determine the effect of visitor density from the existence of the square as a public open space for street vendors in the Probolinggo City Square area. The method in this study used descriptive qualitative data collection techniques, namely interviews, observation and documentation. The main informants in this study were street vendors who had been selling in the town square of Probolinggo for a long time. The street vendors relied on their ability to process food to become a very promising business opportunity in a highly consumptive society.The results of this study state that the mobility of the people in the Alun-Alun greatly influences the sustainability of the businesses run by the informants, so that the effective advice that can be implemented by the managers of the Alun-Alun and the City Government of Probolinggo is the need for additional facilities/infrastructure so that visitors are dominated by local people can feel satisfied and comfortable. The Office of Public Works, Spatial Planning, Housing (PUPR) and Residential Areas has a big role because many facilities must be added and repaired in Probolinggo City Square so that in the future Probolinggo City Square can be used as a tourist reference as a tourism recreation space that has an impact on people's lives. traders around the town square of Probolinggo.